QRIS BSI SEBAGAI INSTRUMEN INKLUSI KEUANGAN SYARIAH: DAMPAK DAN KENDALA BAGI UMKM DI MASJID AL-MUNAWAR KOTA TERNATE - Kurniati Yunus; Syaifuddin; Ilham Putra Usmayani; Muh. Sajjaj Sudirman (Program Studi Ekonomi Syariah IAI Darul Ulum Kandangan, 2025)
The adoption of electronic money through the Quick Response Code Indonesia Standard (QRIS) is an important innovation in supporting transaction digitalization, promoting financial inclusion, and strengthening the economic growth of micro, small, and medium enterprises (MSMEs). Bank Syariah Indonesia (BSI) introduced QRIS as a sharia-compliant payment instrument; however, its implementation still faces challenges at the mosque-based MSME level. This study aims to analyze the impact and obstacles of using BSI QRIS among MSMEs in the Al-Munawar Mosque community in Ternate City, focusing on how its application influences business activities and consumer satisfaction. A qualitative descriptive method was employed with four informants consisting of two MSME actors and two consumers, using Miles and Huberman’s interactive data analysis model, which includes data reduction, data display, and conclusion drawing. The findings reveal that before using QRIS, MSMEs experienced difficulties such as losing potential customers due to limited payment options, slow cash transactions, and challenges in separating personal and business finances. After adopting BSI QRIS, MSMEs benefited from increased sales, time efficiency, stronger brand awareness, and improved transaction recording. The only obstacle reported was internet connectivity issues during unfavorable weather conditions, while no significant challenges were found in the registration or transaction process. These results highlight the importance of BSI QRIS as a sharia-based financial inclusion instrument that can enhance the competitiveness of MSMEs in the digital era.